Harmonization of Science Learning Model: An Integrative Framework for Holistic Education - Raihana Aulia Sukhairani; Haris Riadi; Rika Riauwati; M. Zakariya Al Ansori; Muhammad Nurin (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study formulates a Science Harmonization Learning Model to address the long-standing dichotomy between religious knowledge and modern science in Islamic education. Using a descriptive qualitative approach with an integrative literature review, the study analyzed selected sources through content analysis to identify philosophical and pedagogical patterns relevant to model construction. The findings show that an effective harmonization model rests on tauhidic epistemology and can be operationalized through three interconnected components: an integrative curriculum, contextual-reflective learning methods, and a holistic evaluation system. This model aligns scientific inquiry with moral and spiritual values, enabling teachers to connect concepts, daily life, and character formation in a coherent learning process. The study contributes a practical conceptual framework that translates abstract epistemological ideas into classroom procedures at the school level. It also offers implications for Islamic education reform and supports the implementation of humanistic, moderate, and character-oriented learning in line with the Merdeka Belajar policy.